Dehydrating agents sharply reduce curvature in DNAs containing A tracts. - Sprous, D (1995)
The structural basis of DNA curvature remains elusive, because models for curvature based on crystallographic structures of molecules containing A tracts do not agree with any of the models for sequence-directed curvature based on solution studies. Here we demonstrate that the difference is probably due to MPD (2-methyl-2,4-pentanediol), the dehydrating agent commonly used in crystallography. One characteristic signature of curved DNA molecules is that they run anomalously slowly on polyacrylamide gels, appearing to be larger than they actually are. The gel anomalies of three curved DNAs from trypanosome kinetoplast minicircles drop monotonically with increasing MPD concentration, indicating that MPD straightens molecules that are curved in aqueous solution. This is not due to some non-specific effect of MPD on poly(dA) or polypurine tracts, because control molecules containing dA70 and dG43 run normally over the full range of MPD concentrations. Circular dichroism spectra are not affected by MPD, ruling out a conformational change to a structure outside the B-DNA family. The effect is not due to MPD-induced changes in phasing of the curved sequences, because MPD has virtually no effect on the linking numbers of relaxed plasmids containing either curved sequences or dA70. At the concentrations of MPD used in X-ray crystallography, the curvature of DNAs containing A tracts is substantially lower than in solution, which probably explains the ongoing discrepancies between the crystallographic results and models based on solution studies.